1993
DOI: 10.1175/1520-0477-74-10-1828
|View full text |Cite
|
Sign up to set email alerts
|

The Lake Ontario Winter Storms (LOWS) Project

Abstract: Snowstorms generated over the Great Lakes bring localized heavy precipitation, blizzard conditions, and whiteouts to downwind shores. Hazardous freezing rain often affects the same region in winter. Conventional observations and numerical models generally are resolved too coarsely to allow detection or accurate prediction of these mesoscale severe weather phenomena. The Lake Ontario Winter Storms (LOWS) project was conducted to demonstrate and evaluate the potential for real-time mesoscale monitoring and locat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
13
0

Year Published

1994
1994
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 64 publications
(17 citation statements)
references
References 16 publications
4
13
0
Order By: Relevance
“…These data reflect a precipitation-altitude relationship that has been frequently observed downstream of the GSL and other bodies of water (e.g., Hill 1971;Reinking et al 1993;Saito et al 1996;Steenburgh and Onton 2001;Onton and Steenburgh 2001;Steenburgh 2003;Yeager et al 2013). Potential contributors to the increase in precipitation with elevation include the following: 1) increased vertical motions forced by steep terrain, 2) subcloud evaporation and/or sublimation over adjacent lowland areas, 3) advection of slow-falling hydrometeors into downstream terrain, and 4) increased precipitation efficiency due to higher ice-nucleation rates when parcels are lifted to colder temperatures (e.g., Saito et al 1996).…”
Section: E Downstream Orographic Influencessupporting
confidence: 76%
“…These data reflect a precipitation-altitude relationship that has been frequently observed downstream of the GSL and other bodies of water (e.g., Hill 1971;Reinking et al 1993;Saito et al 1996;Steenburgh and Onton 2001;Onton and Steenburgh 2001;Steenburgh 2003;Yeager et al 2013). Potential contributors to the increase in precipitation with elevation include the following: 1) increased vertical motions forced by steep terrain, 2) subcloud evaporation and/or sublimation over adjacent lowland areas, 3) advection of slow-falling hydrometeors into downstream terrain, and 4) increased precipitation efficiency due to higher ice-nucleation rates when parcels are lifted to colder temperatures (e.g., Saito et al 1996).…”
Section: E Downstream Orographic Influencessupporting
confidence: 76%
“…Nearly threequarters of the cases that produced above-average snowfall were associated with inversion heights >2000 m, whereas only one-third of below-average cases surpassed that threshold. This is in agreement with findings from the Lake Ontario Winter Storms Project, which revealed that the height of the capping inversions was a major factor controlling the intensity of LES events (Reinking et al 1993).…”
Section: A Simple Regressionssupporting
confidence: 92%
“…The intensity of LES events has been shown to be a function of several environmental conditions, including the temperature difference between the lake and the overlying air, the fetch (i.e., the distance that the air mass travels over the lake), the unstable layer's depth and wind shear, the strength of the capping inversion, and lifting by topography or dynamic mechanisms (Wiggin 1950;Jiusto et al 1970;Hill 1971;Niziol 1982;Byrd et al 1991;Hjelmfelt 1992;Reinking et al 1993;Lackmann 2001;Laird et al 2003;Evans and Murphy 2008). Additionally, sensible and latent heat fluxes have been shown to be related to lake ice cover; and ice thickness plays an important role in these fluxes (Zulauf and Krueger 2003;Cordeira and Laird 2008;Gerbush et al 2008).…”
Section: Introductionmentioning
confidence: 99%
“…Past investigations of LE snow storms in the Great Lakes region have primarily focused on events that have developed over ice-free regions (e.g., Braham 1983;Reinking et al 1993;Ballentine et al 1998;Kristovich et al 2000). This study presents two LE snow events that occurred downwind of Lake Erie on 12-14 February 2003 and 28-31 January 2004, which lead to maximum snowfall totals of 43 and 64 cm, respectively, in western New York state during time periods when widespread ice cover was present over Lake Erie (Fig.…”
Section: Introductionmentioning
confidence: 99%